Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Trả lời :
Ta có :
\(x^2+2xy+7x+7y+y^2+10\)
\(=\left(x^2+2xy+y^2\right)+\left(7x+7y\right)+10\)
\(=\left(x+y\right)^2+7\left(x+y\right)+10\)
\(=\left(x+y\right)\left(x+y+2\right)+5\left(x+y+2\right)\)
\(=\left(x+y+2\right)\left(x+y+5\right)\)
Hok tốt
a) \(x^2+2xy+7x+7y+y^2+10\)
\(=\left(x^2+2xy+y^2\right)+\left(7x+7y\right)+10\)
\(=\left(x+y\right)^2+7\left(x+y\right)+10\)
\(=\left(x+y\right)^2+2\left(x+y\right)+5\left(x+y\right)+10\)
\(=\left(x+y+2\right)\left(x+y+5\right).\)
b) \(x^2y+xy^2+x+y=2010\)
\(\Leftrightarrow xy\left(x+y\right)+\left(x+y\right)=2010\)
\(\Leftrightarrow11\left(x+y\right)+1\left(x+y\right)=2010\)
\(\Leftrightarrow12\left(x+y\right)=2010\)
\(\Leftrightarrow x+y=\frac{335}{2}\)
\(\Leftrightarrow\left(x+y\right)^2=\frac{112225}{4}\)
\(\Leftrightarrow x^2+2xy+y^2=\frac{112225}{4}\)
\(\Leftrightarrow x^2+y^2+22=\frac{112225}{4}\)
\(\Leftrightarrow x^2+y^2=\frac{112137}{4}.\)
Vậy \(x^2+y^2=\frac{112137}{4}.\)
a,\(x^2+2xy+7x+7y+y^2+10=\left(x^2+2xy+y^2\right)+7\left(x+y\right)+10\)
\(=\left(x+y\right)^2+2\left(x+y\right)+5\left(x+y\right)+10\)
\(=\left(x+y\right)\left(x+y+2\right)+5\left(x+y+2\right)\)
\(=\left(x+y+2\right)\left(x+y+5\right)\)
b,\(x^2y+xy^2+x+y=2010\Rightarrow xy\left(x+y\right)+x+y=2010\)
\(\Rightarrow12\left(x+y\right)=2010\Rightarrow x+y=167,5\)
Ta có:\(x^2+y^2=x^2+2xy+y^2-2xy=\left(x+y\right)^2-2xy=\left(167,5\right)^2-2.11=28034,25\)
b)\(x^2y+xy^2-x-y\)
\(=xy\left(x+y\right)-\left(x+y\right)\)
\(=\left(xy-1\right)\left(x+y\right)\)
b) x2 + 9x + 20 = x2 + 4x + 5x +20 =x(x + 4) + 5(x + 4) = (x + 4)(x+ 5)
a) 7x^2-7y^2-14x+14y= 7 ( x^2 - y^2 ) - 14 ( x+y) = 14 ( 2(x^2) - 2 (x^2))- 28 ( 2x+2y)
= 28 ( 4 ( x^2)-4(y^2))- 28 ( 2x+2y)
= 28 (4(x^2-y^2) - 4(x+y)
= 28 (4( x^2-y^2-x+y ))
= 112 . ( x-y-x+y)
a) 5x2 - 5xy + 7y - 7x = ( 5x2 - 5xy ) - ( 7x - 7y ) = 5x( x - y ) - 7( x - y ) = ( x - y )( 5x - 7 )
b) x2 - y2 + 2x + 1 = ( x2 + 2x + 1 ) - y2 = ( x + 1 )2 - y2 = ( x - y + 1 )( x + y + 1 )
c) 3x2 + 6xy + 3y2 - 3z2 = 3( x2 + 2xy + y2 - z2 ) = 3[ ( x2 + 2xy + y2 ) - z2 ] = 3[ ( x + y )2 - z2 ] = 3( x + y - z )( x + y + z )
d) ab( x2 + y2 ) + xy( a2 + b2 ) = abx2 + aby2 + a2xy + b2xy
= ( a2xy + abx2 ) + ( aby2 + b2xy )
= ax( ay + bx ) + by( ay + bx )
= ( ay + bx )( ax + by )
1.\(x^2-7x+6\)\(=x^2-6x-x+6\)\(=x\left(x-6\right)-\left(x-6\right)\)\(=\left(x-1\right)\left(x-6\right)\)
2.\(y^2+xy-2x^2=y+2xy-xy-2x^2\)\(=y\left(y-x\right)+2x\left(y-x\right)\)\(=\left(y+2x\right)\left(y-x\right)\)
Học tốt !
1. x2 - 7x + 6
= x2 - x - 6x + 6
= x( x - 1 ) - 6( x - 1 )
= ( x - 6 )( x - 1 )
2. y2 + xy - 2x2
= y2 - xy + 2xy - 2x2
= y( y - x ) + 2x( y - x )
= ( y + 2x )( y - x )
x2+xy-7x-7y=x(x+y)-7(x+y)=(x-7)(x+y)